ANALISIS KESTABILAN MODEL MATEMATIKA JUMLAH PEROKOK PENGARUH KENAIKAN HARGA ROKOK DENGAN DINAMIKA AKAR KUADRAT - ZAI, FIDELIS NOFERTINUS; SEMBIRING, ARYL ZULDAUS; VANBASTEN, ARDINAL; NASUTION, ANGGI NOVITA; SINAGA, LASKER PANGARAPAN (E-Jurnal Matematika; Vol 9 No 4 (2020), 2020)
Consumption of cigarettes in large quantities by the public is one of the main concerns in every country because cigarettes contain harmful ingredients that can trigger various diseases .  This journal will explain the mathematical model of the number of smokers affected by rising prices of cigarettes with square root dynamics . The population  is divided into four, composed of potential smokers, occasionally smokers, heavy smokers, and ex-smokers . The results  of the model analysis are that there is a single point of smoker’s endemic equilibrium . If conditions are met, then the endemic equilibrium point of smokers will be asymptotically stable, and over a long period of time there will always be a spread of smokers.